A Profile Study of Sudden Natural Death Cases in Vadodara Region of Central Gujarat (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sudden death is said to be sudden or unexpected when the victim not known to have been suffering fromany dangerous disease, injury or poisoning is found dead or dies within 24 hours after the onset of terminalillness (WHO). Incidences of sudden natural deaths are increasing now a days and specifically in healthyyoung individuals can arise suspicion of foul play. Our study may help to provide epidemiological dataregarding the sudden death that can be used to control disease outbreaks, identifying emerging causes orchanges in disease pattern so that appropriate action can be taken to reduce the morbidity and mortality. Thepresent study undertaken to find the socio-demographic profile (age, sex and religion etc.) of the deceasedof sudden death. This prospective study had been conducted on autopsy cases brought to tertiary healthcenter of Vadodara, Central Gujarat for the period of one year. During study period total 2240 autopsies wereconducted, of which 224 cases (10%) were sudden deaths. Most of the cases were from the 41 - 50 yearsage group. Of the 224 cases, 149 were due to diseases of cardiovascular system and 63 due to diseases ofrespiratory system. We observed that sudden death cases were higher in young age group and cardiovascularsystem was most commonly involved.